Field effect in semiconductor-electrolyte interfaces : application to investigations of electronic properties of semiconductor surfaces - Konorov, P. P. (Princeton, 2006)
"This book presents a state-of-the-art understanding of semiconductor-electrolyte interfaces. It provides a detailed study of semiconductor-electrolyte interfacial effects, focusing on the physical and electrochemical foundations that affect surface charge, capacitance, conductance, quantum effects, and other properties, both from the point of view of theoretical modeling and metrology. The wet-dry interface, where solid-state devices may be in contact with electrolyte solutions, is of growing interest and importance. This is because such interfaces will be a key part of hydrogen energy and solar cells, and of sensors that would have wide applications in medicine, genomics, environmental science, and bioterrorism prevention."--Jacket